Antioxidant and antimicrobial activity in the seeds of Origanum vulgare L. subsp gracile (C. Koch) letswaart and Origanum acutidens (Hand.-Mazz.) letswaart from Turkey - Kursat, M.; Emre, I.; Yilmaz, O.; Erecevit, P. (Consejo Superior Investigaciones Cientificas-Csic, 2011)
The present study determined some biological compounds (fatty acids, vitamins, sterols and flavonoids), radical scavenging capacity and antimicrobial activity of two Origanum L. species of Origanum vulgare L. subsp. gracile (C. Koch) letswaart and Origanum acutidens (Hand.-Mazz) letswaart. Linolenic acid was found to be the main fatty acid in both species, which was followed by palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1 n9), linoleic acid (C18:2 n6) and stearidonic acid (C18:4). In addition, the two Origanum species were recorded as containing high levels of stigmasterol. It was also found that Origanum vulgare L. subsp. gracile (C. Koch) letswaart had a high beta-sitosterol content (152.8 +/- 2.6 mu g/g); high amounts of D3 (33.1 +/- 0.8 mu g/g), K1 (29.4 +/- 0.8 mu g/g), K2 (26.0 +/- 0.8 mu g/g) vitamins; and low amounts of alpha-tocopherol (7.8 +/- 0.2 mu g/g) and D2 (1.8 +/- 0.1 mu g/g), while Origanum acutidens (Hand.-Mazz.) letswaart contained high amounts of D2 (42.9 +/- 1.5 mu g/g) vitamin; and low amounts of D3 (2.9 +/- 0.1 mu g/g), alpha-tocopherol (3.1 +/- 0.1 mu g/g), r-tocopherol (3.5 +/- 0.2 mu g/g), K2 (1.3 +/- 0.1 mu g/g), retinol (1.3 +/- 0.2 mu g/g) and retinol acetate (1.2 +/- 0.1 mu g/g) vitamins. The present study showed that Origanum vulgare L. subsp. gracile (C. Koch) letswaart and Origanum acutidens (Hand.-Mazz.) letswaart contained the lowest amount of flavonoid. Furthermore, methanol extracts were recorded to be the most effective agent against the DPPH radical in both Origanum L. species examined. Experimental results showed that the vitamins, flavonoids and fatty acid extracts of both Origanum L. species were effective in the inhibition of the growth of the tested microorganisms at varying levels.
Keywords: Antimicrobial capacity; DPPH radical scavenging activity; Fatty acids; Flavonoids; Origanum L.; Sterols; Vitamins